The Concept of the Family in Modern Society and its Main Tasks in the Republic of Uzbekistan - Abulova M.K. (Zien Journals, 2023)
The article examines the issues: legal and sociological concept families; The main tasks of the family; family protection by society and government family law of foreign countries, etc. The concept of family law; the role and place of family law in the legal system; principles of family law; a system of family law
Keywords: Law; family law; system of family law